The white archer : an Inuit-Eskimo legend - Houston, James A., 1921- (San Diego : Harcourt Brace Jovanovich, 1990)
A young Eskimo vows to avenge his parents' violent death and the kidnapping of his sister, but over the years it takes him to become a master archer he outgrows his hatred.
7.1
3-6
Keywords: Eskimos -- Legends -- Juvenile literature; Eskimos -- Legends; Indians of North America -- Folklore; Inuit -- Legends; Indians of North America -- Folklore